Trafficking of Women and Children in East Nusa Tenggara Province as the Defeat of Subsistent Community to Market Economy of Migrant Labour - Li, Dominggus Elcid (Yayasan Jurnal Perempuan, 2020)
The analytical view exploers in this paper represent the perspective of subsistent farmers in NTT Province when integrated with market economy. It tries to explain why the subsistent community are so vulnerable to become migrant workers and uprooted from their land; it is also attempt to investigate the relation between economic policy on free labour market with death and torture received by migrant workers. While the victims, especially women and children, are publicized and attracted attention from mass media and also social media. However, the publication over the suffering of migrant workers from the margin of Indonesia such as NTT Province, does not get direct impact over the policy makers with the willingness to renew regulation to protect migrant workers. This paper focuses on investigating why the poor migrant women and children are being neglected by policy makers under the neoliberalorder. It also tries to explain why the subsistent members are easily uprooted from their land and become migrant workers during modernization. It also tries to answer why the are often in position as the losers or victims during globalization. The hope that the State is able to protect the vulnerables is fading away under the domination of pro market policy. Children and women as the silent victims are the evidence of absolute surrender of the subsistent community. State incapacity to protect the most vulnerable citizens is the evidence of the coming of new wave of neocolonialism. This is also a proof the modernization is also part of conquering whenhalf-hearted modernization has placed them at the bottom of the pyramid of modernity which is vulnerable to be exploited without the ability to speak and to be listened.Â Â